Electromagnetic Radiation: Variational Methods, Waveguides and Accelerators
DOI: 10.1007/3-540-29224-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Quantum Theory of Synergic Synchrotron-Čerenkov Radiation

Abstract: The power spectra of C 8 erenkov, synchrotron, and synchrotron C 8 erenkov radiation are calculated both classically (by source methods) and quantum mechanically (by mass operator methods). The synergic features of the synchrotron C 8 erenkov radiation are pointed out. The existence of a transition region near n;=1 [n(|, H)=index of refraction of the medium; ;=vÂc, v=velocity of the charged particle] coupled with the intrinsic dispersion of the medium is then applied to the discussion of the suppression of X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A 1957 review paper described the ČR from particles with different spins [28]. Another 1957 paper [29] studied how two-photon emission affects ČR, with later work providing observation of such corrections arising from higher-order Feynman diagrams [30] and effects of external magnetic fields [31]. However, to the best of our knowledge, all previous research always reconfirmed the same classical limit found by Čerenkov, Frank and Tamm [1,24].…”
Section: Introductionmentioning
confidence: 61%
“…A 1957 review paper described the ČR from particles with different spins [28]. Another 1957 paper [29] studied how two-photon emission affects ČR, with later work providing observation of such corrections arising from higher-order Feynman diagrams [30] and effects of external magnetic fields [31]. However, to the best of our knowledge, all previous research always reconfirmed the same classical limit found by Čerenkov, Frank and Tamm [1,24].…”
Section: Introductionmentioning
confidence: 61%
“…As the polarization and magnetization in (2.9) are cubic on external fields, the electromagnetic waves and charged particles propagation in perturbative QED vacuum will possess the properties peculiar to crystal optics with cubic nonlinearity. This approach leads to the predictions for vacuum birefringence and dichroism [16][17][18], optical non-reciprocity [19], light-ray bending [20,21] and Cherenkov-radiation [22,23] in vacuum at presence of external electromagnetic field. The expansion of these predictions on nonperturbative QED regime gives a new insight in understanding of vacuum nonlinear electrodynamics and helps to enforce the expectations in experimental manifestations.…”
Section: Jhep05(2017)105mentioning
confidence: 99%
“…Source theory [6,[30][31][32] is the theoretical construction which uses quantum-mechanical particle language. Initially it was constructed for description of the particle physics situations occurring in the high-energy physics experiments.…”
Section: The Source Theory Of Thečerenkov Effectmentioning
confidence: 99%
“…It may be easy to show that the probability of the persistence of vacuum is given by the following formula [30]:…”
Section: The Source Theory Of Thečerenkov Effectmentioning
confidence: 99%
See 1 more Smart Citation